Effective stress method on threshold stress of clay under high rate cyclic loading - Loh, R.; Nikraz, Hamid (2012)
This paper discussed the undrained triaxial testing of soft clay which may be encountered as subgrade soil in the alignment of railway track or road pavement. Several series of both static and cyclic undrained triaxial test were conducted. The static undrained triaxial test provides a prior indication on the maximum stress level from which the cyclic stress level can be apportioned. The cyclic undrained triaxial test simulates the behaviour of clay subgrade under the passing train axle's loading. The analysis of test results showed the feasible use of "effective stress" analysis in establishing threshold stress for clay under high cyclic loading rate. The study reaffirmed the influence of stress history on the level of threshold stress. In particular, cyclic stress ratio (CSR) of threshold stress was found reducing with higher over-consolidation ratio. The threshold stress so obtained represents the lower-bound bearing strength for unsaturated clay subgrade of railway track.